Atmospheres of (counter) terrorism survey, 2022 - Heurtel, H. (UK Data Service, 2024)
The project is an unprecedented, large-scale qualitative and quantitative international comparison of how counterterrorism and urban security interact with our everyday experience of cities in Europe. The project is based upon an international questionnaire survey focused on perceptions of terrorist threat in the ordinary experience of the urban space and the daily activities of the inhabitants of France, Germany, and the UK, and in-depth research in 5 European cities with contrasting histories of attacks, threat level, and planning/policy responses (Berlin, Birmingham, Nice, Paris, and Plymouth). It engages with urban residents and stakeholders involved in urban security/planning. The project adds empirical knowledge to ongoing scholarly debates in social and cultural geography and urban geopolitics. Moreover, the project will provide key insights for practitioners (urban planners, security agencies and the wider public). This allows to produce original and usable evidence on how counterterrorism impacts on the shared felt qualities (atmosphere) of urban spaces. This collection contains the data from a survey on a representative sample of people from France, Germany and the United Kingdom in 2022 regarding the evolution of their opinions, practices, perceptions, and representation of public space in relationship to terrorism and counterterrorism. Terrorism is a profoundly urban phenomenon. In this project, we define terrorism as ideologically motivated acts of violence which are directed towards a general population, seeking to produce fearful feelings beyond those directly impacted by that act. Compared to other world regions, Europe scores relatively low in absolute numbers of terrorist attacks. However, cities in Europe are increasingly redesigned in a militarised fashion in response to such attacks and future threats. For example, functions traditionally associated with state boundaries (border control, mobility monitoring, army patrolling) are becoming an increasingly integral part of the policy discourse, spaces, and infrastructures of urban security. The urbanisation of terror involves a substantial change in how terrorists operate, shifting away from high-profile attacks against securitised spaces, and attacking instead 'soft targets' (everyday spaces e.g. Christmas markets, shopping promenades, pavements, hotels, restaurants, or cafes) which are difficult, if not impossible, to secure. Attacks against such spaces can be conducted via unsophisticated preparation and weaponry. The security of soft targets cannot be achieved via traditional planning focused on hardening infrastructure, without also altering the experience of public space. In other words, in the face of terrorism urban public spaces undergo not only deep physical and material changes, but are also changed atmospherically - that is to say, in their felt quality as shared spaces. As such, we argue that there is more to security and counterterrorism in cities than hardened infrastructures, security barriers, emergency operations, house raids, and lockdowns. What we still don't know in detail or systematically, is how counterterrorism is changing the experience of the city for millions of urban residents. We therefore adopt the notion of atmosphere as a means of thinking through and interpreting the individual and collective felt experiences of urban residents amidst counter-terror measures and terror threats. Practically, the problem we tackle is: what do atmospheres do to places and bodies? What are they an effect of and what effects do they have? What power do they have to make people act and think? Specifically, the project asks: - How do terror threats and security responses change the atmosphere of public space in European cities? - What are the atmospheric implications of counterterrorism for social encounters in crowded public spaces in European cities? - How does the felt experience of counterterrorism and security translate across diverse urban communities? - How can we operationalise atmosphere as a conceptual lens and methodical tool through which to improve the everyday experience of urban security and counterterrorism?